Performance Modification and Application Of Poly (Lactic Acid)-Based Biodegradable Biomaterials - Zhang, Xincheng (Transactions on Computer Science and Intelligent Systems Research, 2024)
As new type of biodegradable material, polylactic acid (PLA) is synthesized by plant resources. This material features high mechanical properties, biocompatibility and biodegradability. It is mainly used in agriculture, medicine, biology, environmental protection, engineering and other fields. With the progress of science and technology, new requirements and applications have been put forward for the properties of PLA material, thus it must be modified to improve its processing and application properties. Only higher performance polylactic acid based materials can meet the growing needs of production and life. This review summarizes the research progress of PLA performance improvement from both physical modification and chemical modification, involving blending modification, plasticizing and toughening modification, composite modification as well as copolymerization modification, cross-linking modification and other modification methods, and introduces the research progress in the fields of agriculture, food, engineering. Furthermore, it is aimed at providing certain references for the broadening of PLA application market and discusses the future development trends of PLA.